Relationship Between Workers’ Knowledge and Attitudes With The Risk Of Work Accidents at 31 Rice Mill Centers in Kaway XVI Sub-District, West Aceh District. - Yolanda Oktaria; Daru Lestantyo; Hanifa Maher Denny (Universitas Teuku Umar, 2021)
Risk is the probability that something occurs and has an impact on the goal. Risk is measured according to its likelihood and consequences of injury and illness as well as the severity of the damage or loss/injury. This study aims to analyze the factors of workers’ knowledge and attitudes towards the risk of work accidents in the informal sector. This study used a case-control method by comparing groups of workers who have experienced work accidents with those who have not experienced work accidents. The results showed that there was a relationship between occupational health and safety knowledge factors and the risk of work accidents in 31 rice milling centers with a p-value of 0.000 <0.05 and there was a relationship between workers' attitudes towards the risk of work accidents in 31 rice milling centers with a p-value of 000 <0.05. It suggests the need for socialization, education and information about risk factors of work accidents in 31 rice milling centers..